Impact of the Coronavirus disease pandemic on early breast cancer - Yong Li; Yong Li; Xiao-ju Lu; Bo Xu; Bo Xu; Wei-wen Li (Frontiers in Oncology)
ObjectiveTo assess the impact of the COVID-19 pandemic on the presentation, treatment, and survival of patients with early breast cancer (Stage I–III).MethodsThis study utilized data from the Surveillance, Epidemiology, and End Results database from January 1, 2018, to December 31, 2020. Patients diagnosed with primary breast cancer in 2020 were compared to those diagnosed in 2018 or 2019. The primary outcomes were stage distribution and changes in the treatment modalities for early breast cancer. The secondary outcomes were overall survival (OS) and breast cancer-specific survival (BCSS).ResultsWe analyzed 142,038 patients. There has been a decrease in breast cancer diagnoses in 2020, as well as the smaller number of surgeries. The distribution of breast cancer stages among patients exhibited a notable shift in 2020, with a decrease in the proportion of Stage 0-I and an increase in advanced-stage. Additionally, there was a significant decrease in the proportion of breast-conserving surgery (BCS) performed in 2020. The proportion of patients undergoing radiation decreased, while that of chemotherapy cases increased significantly in 2020. Patients showed a shorter treatment delay in 2020 than in 2018 or 2019 (2018: hazard ratio [HR] = 0.969, 95% confidence interval [CI] = 0.956–0.982, p < 0.001; 2019: HR=0.959, 95% CI = 0.946–0.972, p < 0.001). Diagnosis in 2020 showed a significant correlation with worse OS than diagnosis in 2018 (HR = 0.861, 95% CI = 0.743-0.996, p = 0.045).ConclusionWe observed a shift to advanced-stage and a change of treatment modalities of early breast cancer in 2020. The OS of patients with breast cancer was worse during the pandemic than before the pandemic. The findings could provide empirical basis for optimizing cancer prevention and control strategies in future public health emergencies.